The electronic structure of ion beam mixed ferromagnetic multilayered films - Chang, GS; Kim, SH; Chae, KH; Kurmaev, EZ; Galakhov, V; Moewes, A; Lee, YP; Jeong, K; Whang, CN (ELSEVIER, 2001)
The electronic structure of ion beam mixed Co/Pt multilayered films was investigated using synchrotron-based soft X-ray fluorescence (SXF) and photoemission spectroscopy (PES). Co/Pt multilayered films (eight periods of Co and Pt sublayers) were prepared on Si(100) substrates by alternating electron-beam evaporation followed by ion beam mixing with 80 keVAr ions under high vacuum. The SXF and PES measurements show that ion beam mixing can change the spectral features of Co 3d valence bands for PES spectra and the emission energies for Co L-3 SXF spectra. The similar valence-band characteristics of IBM CoPt3 with pure Co and the low emission energy with respect to stable CoPt3 alloy are correlated with the isolated Co 3d states with a weakened interatomic interaction due to the reduced coordination. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: PERPENDICULAR MAGNETIC-ANISOTROPY; X-RAY PHOTOEMISSION; MAGNETOOPTICAL PROPERTIES; CO/PT; AG; PD